SAE Technical Paper Series 1998
DOI: 10.4271/982484
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Charge Compression Ignition with a Free Piston: A New Approach to Ideal Otto Cycle Performance

Abstract: Sandia National Laboratories has been investigating a new, integrated approach to generating electricity with ultra low emissions and very high efficiency for low power (30 kW) applications such as hybrid vehicles and portable generators. Our approach utilizes a free piston in a double-ended cylinder. Combustion occurs alternately at each cylinder end, with intake/exhaust processes accomplished through a two stroke cycle. A linear alternator is mounted in the center section of the cylinder, serving to both gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(70 citation statements)
references
References 22 publications
1
68
0
Order By: Relevance
“…Several studies on four stroke engines have also been carried out [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. High efficiency and low NOxemissions are reported, but emissions of unburned hydrocarbons are high.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on four stroke engines have also been carried out [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. High efficiency and low NOxemissions are reported, but emissions of unburned hydrocarbons are high.…”
Section: Introductionmentioning
confidence: 99%
“…This reduces heat loss and lowers the combustion temperature, thus producing low NOx. Van Blarigan [9] measured the thermal efficiency of an FPLG at 56% with low NOx emissions compared with the conventional crank engine whose efficiency is lower than 40%. Fredriksson [10] found similar characteristics and showed that most combustion occurred at fast expansion rate and below 1800 K which is enough to ensure an ultra-low level of NOx.…”
Section: Free-piston Linear Generator Enginementioning
confidence: 99%
“…Figures 24,25, and 26 show the results for n-heptane. An equivalence ratio of 0.334 and an initial temperature of 24OC were used.…”
Section: At An Initial Temperaturementioning
confidence: 99%
“…An equivalence ratio of 0.321 was used at initial temperatures of 25 and 7OoC. Isooctane, like propane and natural gas, burned in a single step process and at nearly constant volume, as can be seen in Figure 27.…”
Section: At An Initial Temperaturementioning
confidence: 99%